O uso da Web como corpus em pesquisas fraseológicas: Uma prática prejudicial ou um recurso valioso? - Valença, Eloísa Moriel [UNESP]; Sabino, Marilei Amadeu [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2016)
This paper intends to present the methodological approach used in the search for Idiomatic Expressions of Metaphorical Low-Deductible (EIBDM) found in Italian dictionaries of phraseologisms. By Idiomatic Expressions of Metaphorical Low-Deductible, we mean those combinatorial expressions in foreign language which presents, in its constitution, historical, geographical, religious, mythological, weather (temporal) or simply linguistic elements, explicit or implicit, that are typical or significant only in the source language or in the native language (in our case, the Italian).This means that its semantic material does not help or provide clues to the translation process in the target language (in the case of this research, the Brazilian variant of the Portuguese). We also discuss the importance of Corpus Linguistics for phraseological studies and the relevance of using the Web as Corpus (WAC) in phraseological and lexicographical research. Despite its limitations, the Web as Corpus is a valuable tool to attest frequency, contexts of use, syntactic and semantic behavior of idiomatic expressions in different contexts.
Using web as corpus in phraseological researches: A damaging practice or a valuable resource?
Keywords: Idioms; Low metaphorical deductibility; Metaphor; Web as corpus (wac)